The view from Bald Hill : thirty years in an Arizona grassland - Bock, Carl E., 1942- (Organisms and environments, 2000)
In 1540 Francisco Vasquez de Coronado introduced the first domestic livestock to the American Southwest. Over the subsequent four centuries, cattle, horses, and sheep have created a massive ecological experiment on these arid grasslands, changing them in ways we can never know with certainty.